Adaptive Current Differential Protection Method Considering Control and Protection Coordination - Bo ZHANG; Congbo WANG; Rongrong ZHAN; Yue YU (Zhongguo dianli)
The VSC-HVDC transmission system for large-scale new energy has become a typical scenario in China's new power system. However, the transmission line between the new energy station and the flexible direct converter is special with its both sides being power electronic devices, and affected by different converter control strategies, the short-circuit current waveform is seriously distorted, which reduces the sensitivity of traditional longitudinal protection and increases the risk of rejection. Therefore, an adaptive current differential protection method considering control and protection coordination is proposed. Based on the fault ride throgh strategy of the VSC-HVDC, the fault current characteristics on both sides are analyzed, and an adaptive protection criterion for control and protection coordination is constructed by combining the control reference value of the converter and the protection criterion. Finally, a VSC-HVDC transmission system model for new energy is built based on PSCAD, and the performance of the proposed protection is verified by simulation. The results show that the proposed protection can quickly identify different fault types in the fault region with the sensitivity improved by 2~3 times compared with the traditional differential protection principle, which can meet the requirements of the new power systems for protection sensitivity and reliability.